Preventative Prophetic Guidance in Infection and Quarantine - Goje, Kabiru (Jurnal Usuluddin, 2017)
Medical treatment is one of the most important means for preventing communicable diseases in the modern time. In this situation, a person is prevented from entering a location that is infected by this disease to prevent its spread. In equal vain, the people of that location are prevented from getting out of it; weather such a person is infected or not. However, Quarantine is considered in the contemporary time as one of the human preventative mechanism from the spread of infectious diseases and the reason being that it is used in containing and controlling the risk of outbreaks. This is one of the humiliating tests from Allah the Highest on human, and shows the mightiness of His mercy. Hence, the Use of Quarantine has achieved a great significance in preventing spread of diseases because it is a primary means for combating communicable diseases in the world. Our goal and objective are to provide access to scientifically sound and culturally acceptable information on health promotion and disease prevention, to all those who need it, using the information from Prophetic Traditions. The methodology in this research to examine the concept of infection and quarantine in the light of the Prophetic traditions so that the relationship between these two concepts and the Prophetic traditions will be distinctly explained by using the data from many Islamic books, journals and articles relevant to Prophetic Islamic medicine and contemporary medicine. The result of this study revealed that the Holy Prophet (peace be upon him) was so concerned about every aspect of human life including that of health. This was yielded from prophetic traditions that infused preventive knowledge, which if humans could have made proper use of it, they would be prevented from many illness and healed others. In conclusion, the study addresses prophetic traditions that are related to preventive medicine about infection and quarantine, and support these prophetic traditions by contemporary doctors’ opinions, which are attested by the fact, or are proved by experiments that accounts for non-violation of the Sharia.